Equity valuation : Amadeus - Garcia, Miguel Pereira da Silva Stapleton (2012)
From Finance to Corporate Strategy, valuation is the word of the day. Applied to all fields, valuation techniques improved over time, currently being the subject of intensive academic research and professional use. Nevertheless, objective comparison between academic and professional valuations of a specific asset or company has been a topic with limited attention. This thesis purposes to show empirical evidence on how valuations between these two worlds lead to different results, by valuing the Amadeus IT Group, the leading technology provider for both global travel and tourism industries, and comparing it to Espírito Santo Investment Bank equity research report. To do so, I will use the appropriate valuations approaches found under the contemporary and relevant literature review on the theme.